Application of a definitive screening design for the synthesis of a charge-transfer complex of sparfloxacin with tetracyanoethylene: spectroscopic, thermodynamic, kinetics, and DFT computational studies. Issue 43 (8th August 2019) - El-Shafie, Ahmed S.; Khashan, Areej W.; Hussein, Yasser H. A.; El-Azazy, Marwa
Abstract : A spectrochemical approach was adopted to study the charge-transfer (CT) complexation of sparfloxacin (SFX) with tetracyanoethylene (TCNE). Definitive screening design (DSD) was used to investigate the reaction variables. Abstract : Herein, a spectrochemical approach was adopted to study the charge-transfer (CT) complexation of sparfloxacin (SFX) with tetracyanoethylene (TCNE). In this study, a three-level design of experiments (DOE) involving a definitive screening design (DSD) was implemented. This is the first effort to operate this new category of design to determine a pharmaceutical compound in its pure form and in formulations. The proposed design allowed the establishment of a regression model that described the relation between the factorial input and the response surface. Moreover, two charge-transfer states (CTSs) were observed at 390 and 464 nm. The DFT calculations conducted using B3LYP/6-31+G showed that SFX had several donation sites (donor, D), whereas TCNE had two acceptor (A) sites. The two states were influenced differently by the experimental conditions as per the findings of the DSD analysis. In general, the diluting solvent had the largest impact. Probability plots, histograms, individual value plots, residual plots as well as analysis of variance (ANOVA) were delineated at the 95.0% confidence interval (CI). A Job's plot showed that a 1 : 1 complex was formed. The results were further confirmed using Benesi–Hildebrand plots. The proposed approach was proved to be linear in the range of 10–90 μg mL −1 SFX when the absorbance was measured at 464 nm. Different set-ups were adopted for studying the reaction kinetics. Analytical method performance was assessed following the ICH guiding principles, and the results obtained were found to be satisfactory. Complex formation was found to be an exothermic reaction.